(z+7)(z+3)=0

Simple and best practice solution for (z+7)(z+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (z+7)(z+3)=0 equation:


Simplifying
(z + 7)(z + 3) = 0

Reorder the terms:
(7 + z)(z + 3) = 0

Reorder the terms:
(7 + z)(3 + z) = 0

Multiply (7 + z) * (3 + z)
(7(3 + z) + z(3 + z)) = 0
((3 * 7 + z * 7) + z(3 + z)) = 0
((21 + 7z) + z(3 + z)) = 0
(21 + 7z + (3 * z + z * z)) = 0
(21 + 7z + (3z + z2)) = 0

Combine like terms: 7z + 3z = 10z
(21 + 10z + z2) = 0

Solving
21 + 10z + z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(7 + z)(3 + z) = 0

Subproblem 1

Set the factor '(7 + z)' equal to zero and attempt to solve: Simplifying 7 + z = 0 Solving 7 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + z = 0 + -7 Combine like terms: 7 + -7 = 0 0 + z = 0 + -7 z = 0 + -7 Combine like terms: 0 + -7 = -7 z = -7 Simplifying z = -7

Subproblem 2

Set the factor '(3 + z)' equal to zero and attempt to solve: Simplifying 3 + z = 0 Solving 3 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + z = 0 + -3 Combine like terms: 3 + -3 = 0 0 + z = 0 + -3 z = 0 + -3 Combine like terms: 0 + -3 = -3 z = -3 Simplifying z = -3

Solution

z = {-7, -3}

See similar equations:

| 2c+an-3d= | | 9-2t=-1-3t | | 120-30+6x=2x-60 | | -41=-0.4(45n+60)+n | | -10x+2y+10=0 | | 2x-13=13-8x+14 | | -1+6x-6=23 | | 3y-5x=x+9 | | 5x-2/3-6 | | x^2+14-7=0 | | 6n+n=2860 | | 0.2x+5.7+4.9=10.2266 | | 4a+r= | | 26x-24=56 | | v^2=2 | | g-78=876 | | 6c-8-2c=-7 | | 0.17x-0.4(x+1700)=-2556 | | 20/0= | | 2t+2.2H=-3.7 | | X-108=36 | | x+3y-3z=-26 | | 2(6x+8)-2(3x-6)= | | 3x-8=-2(4x-2) | | H-3.5=5 | | 9(-5/8) | | 23.42-x=15.42 | | 4.12-c=2.45 | | -8x-14y=52 | | 4x+34+6x-14=180 | | 1-3/2x=5/6 | | 7x-(2x+5)=3x+7 |

Equations solver categories